Long-term reinfection of the human genome by endogenous retroviruses - Belshaw, Robert (National Academy of Sciences, 2004)
Endogenous retrovirus (ERV) families are derived from their exogenous counterparts by means of a process of germ-line infection and proliferation within the host genome. Several families in the human and mouse genomes now consist of many hundreds of elements and, although several candidates have been proposed, the mechanism behind this proliferation has remained uncertain. To investigate this mechanism, we reconstructed the ratio of nonsynonymous to synonymous changes and the acquisition of stop codons during the evolution of the human ERV family HERV-K(HML2). We show that all genes, including the env gene, which is necessary only for movement between cells, have been under continuous purifying selection. This finding strongly suggests that the proliferation of this family has been almost entirely due to germ-line reinfection, rather than retrotransposition in cis or complementation in trans, and that an infectious pool of endogenous retroviruses has persisted within the primate lineage throughout the past 30 million years. Because many elements within this pool would have been unfixed, it is possible that the HERV-K(HML2) family still contains infectious elements at present, despite their apparent absence in the human genome sequence. Analysis of the env gene of eight other HERV families indicated that reinfection is likely to be the most common mechanism by which endogenous retroviruses proliferate in their hosts.